Out of bounds : sports in the inner city - Smith, Stephen A. (Stephen Anthony), 1967-; Macmillan, Jackie; Jackson, Robert, 1963 November 22-; Rateau, Noube; Medero, William; Noube Productions; Leomark Studios (Firm) ([Brockton, Mass.] : Noube Productions., 2015)
This Emmy Nominated documentary brings together for the first time some of the largest local and national names in sports. ESPN's Stephen A Smith, Jackie Macmillan, and Robert "Scoop" Jackson give their perspectives on the importance of athletes and finding success after sports. Basketball Division 1 standout Brian Rudolph (New Bedford), All American Matt King (Stoughton), All Conference Kharee Louis Jeune (Brockton), and others are chronicled about their life in the toughest parts of the city and how sports was their ticket out.
Originally released as a motion picture in 2015
Analysts: Stephen A. Smith, Jackie Macmillan, Robert "Scoop" Jackson.
Narrators: Dennis Wilson, Darius Heywood, Dan Martinez, Marcel Smith.
Editor, Noube Rateau.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 20, 2017).
Keywords: Basketball players -- United States; Career changes; Urban youth -- United States; Sports films; Documentary films; Nonfiction films; Feature films; Internet videos; Streaming video